Iraq war : the essential reference guide - Steed, Brian L. (Gale virtual reference library, 2019)
This book offers an overview of the Iraq War, with articles by leading scholars plus key primary source documents. It discusses the Bush administration's decision to invade Iraq, the U.S. troop surge in 2007, and the rise of the Islamic State. It offers insight through events, organizations, and people who had an impact on the conflict, plus inadvertent consequences, including worsening regional sectarian divisions, Arab Spring, expansion of international terrorism and more.